Comparative Characterization of Indonesian AISI 316L Stainless Steel and Commercial Femoral Stem for Artificial Hip Joint Applications - Mujib Wahyudi; Rifky Ismail (Jurnal Konversi Energi dan Manufaktur, 2026)
The development of the femoral stem, part of the artificial hip joint, requires a material with microstructures, mechanical properties, and chemical composition that meet the requirements of a medical implant. This study aims to characterize and compare Indonesian AISI 316L stainless steel with two commercial femoral stem implants used by patients, namely XYZ products from the United States and ABC products from India. The tests carried out on the three products include tensile tests, macro hardness, microhardness, microstructure observations, and chemical composition analysis. The tensile test results show that XYZ products have the highest ultimate tensile strength (UTS) of 1065.6 ± 11.7 MPa, while the Indonesian AISI 316L (IDN) and ABC products showed lower UTS values of 580.9 ± 0.3 and 536.3 ± 9.4 MPa, respectively. Microhardness tests showed that XYZ products achieved the highest hardness value of 306.0 ± 13.5 VHN with an increasing hardness gradient towards the surface. Meanwhile, the Indonesian AISI 316L materials showed a relatively homogeneous hardness distribution with an average value of approximately 197.5 ± 1.3 VHN. Observation of microstructures reveals differences in grain size and distribution, which correlate with microhardness values. Analysis of the elemental composition shows that all three materials exhibit characteristics of austenitic stainless steel with variations in the alloy element content. Overall, the results highlight the influence of microstructural features and alloy composition on mechanical performance. Although the Indonesian AISI 316L material evaluated in this study is not classified as implant-grade stainless steel, the findings provide a baseline reference for future material development. It emphasizes the need for strict compliance with implant-grade standards, manufacturing optimization, and surface treatment to enable potential application in femoral stem component.